2003
DOI: 10.1002/art.11368
|View full text |Cite
|
Sign up to set email alerts
|

Reactive hemophagocytic syndrome in adult systemic disease: Report of twenty‐six cases and literature review

Abstract: Objective. To analyze specific clinical findings, underlying disorders, treatments, outcomes, and prognostic factors for reactive hemophagocytic syndrome (RHS) in systemic disease. Methods. Data were collected using standardized forms as part of a French national survey. Adult cases without an underlying malignancy, diagnosed on bone marrow or lymph node biopsy, were included. Results. Twenty-six cases (7 men, 19 women, mean age 47.4 ؎ 17.7 years) were studied. Systemic diseases included systemic lupus erythem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
190
1
22

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(230 citation statements)
references
References 32 publications
5
190
1
22
Order By: Relevance
“…The prevalence of MAS was 1.4% among all patients followed at our center, and was similar to that reported in the literature in adult SLE patients (3)(4)(5)(6). In our experience, in all cases MAS was diagnosed in untreated SLE patients with active disease.…”
Section: N Discussion and Conclusionsupporting
confidence: 89%
See 2 more Smart Citations
“…The prevalence of MAS was 1.4% among all patients followed at our center, and was similar to that reported in the literature in adult SLE patients (3)(4)(5)(6). In our experience, in all cases MAS was diagnosed in untreated SLE patients with active disease.…”
Section: N Discussion and Conclusionsupporting
confidence: 89%
“…Although in our experience, MAS and SLE were diagnosed simultaneously and this was also the most frequent scenario in some other previous series (4,8), recent data indicate that MAS may arise in patients with long disease duration in up to 50% of the cases (7). 3 and/or a platelet count of <110,000/mm 3 ; °the cut-off suggested for the classification of reactive MAS in the original study was 169 (11). Other authors suggested a higher cutoff (190.5), in patients with rheumatic diseases (15).…”
Section: N Discussion and Conclusionmentioning
confidence: 94%
See 1 more Smart Citation
“…1,3 Hemophagocytic lymphohistiocytosis-like episodes were also described in association with systemic lupus erythematosus, rheumatoid arthritis, polyarteritis nodosa, mixed connective tissue disease and others. 18,19 These patients may be considered as having 'secondary or acquired' HLH, commonly referred to as MAS in the rheumatologic literature. Macrophage activation syndrome shares many clinical/ laboratory features with HLH, and several authors classify MAS as 'secondary' or 'acquired' hemophagocytic syndrome.…”
Section: Macrophage Activation Syndromementioning
confidence: 99%
“…It is important to bear in mind that AOSD may begin with an HS [42]. Furthermore, malignant lymphoma should not only be excluded for diagnosis, but they may be added to the large variety of complications associated with this disease [43].…”
Section: Clinical Featuresmentioning
confidence: 99%